Impact of ethnicity on adverse perinatal outcome in women with chronic hypertension: a cohort study. (9th July 2019) - Webster, L. M.; Bramham, K.; Seed, P. T.; Homsy, M.; Widdows, K.; Webb, A. J.; Nelson‐Piercy, C.; Magee, L.; Thilaganathan, B.; Myers, J. E.; Chappell, L. C.
ABSTRACT: Objective: To assess the impact of maternal ethnicity on the risk of adverse perinatal outcome in pregnant women with chronic hypertension. Methods: Demographic and delivery data were collated of women with chronic hypertension and singleton pregnancy who delivered at one of three UK obstetric units between 2000 and 2014. Multivariable logistic regression models were used to calculate risk ratios (RR), according to ethnic group, for adverse perinatal outcome, adjusted for other maternal characteristics including age, parity, body mass index, smoking status, deprivation index and year of delivery. The impact of maternal ethnicity on birth‐weight centile calculation was investigated by comparing the birth‐weight centile chart customized for ethnicity (Gestation Related Optimal Weight; GROW) with a birth‐weight centile calculator that does not adjust for that factor (INTERGROWTH‐21 st ). Results: The study cohort included 4481 pregnancies (4045 women) with chronic hypertension. Women of white ethnicity accounted for 47% ( n = 2122) of the cohort and 36% ( n = 1601) were of black, 8.5% ( n = 379) of Asian and 8.5% ( n = 379) of other ethnicity. The overall incidence of stillbirth was 1.6%, that of preterm birth < 37 weeks was 16% and that of fetal growth restriction (birth weight < 3 rd centile) was 11%. Black women, compared with white women, had the highest risk for all adverse perinatal outcomes, with stillbirth occurring in 3.1% vs 0.6% of pregnancies (adjusted RR (aRR), 5.56 (95% CI, 2.79–11.09)), preterm birth < 37 weeks in 21% vs 11% (aRR, 1.70 (95% CI, 1.43–2.01)) and birth weight < 3 rd centile in 15% vs 7.4% (aRR, 2.07 (95% CI, 1.71–2.51)). Asian women, compared with white women, were also at increased risk of adverse perinatal outcome, with stillbirth occurring in 1.6% vs 0.6% (aRR, 3.03 (95% CI, 1.11–8.28)), preterm birth < 37 weeks in 20% vs 11% (aRR, 1.82 (95% CI, 1.41–2.35)) and birth weight < 3 rd centile in 12% vs 7.4% (aRR, 1.69 (95% CI, 1.24–2.30)). The sensitivity and specificity for prediction of infants requiring neonatal unit admission were 40% and 93%, respectively, for those with birth weight < 3 rd centile according to GROW charts, compared with 16% and 96%, respectively, for those with birth weight < 3 rd centile according to INTERGROWTH‐21 st charts. Conclusions: Black ethnicity, compared with white, is associated with the greatest risk of adverse perinatal outcome in women with chronic hypertension, even after adjusting for other maternal characteristics. Women of Asian ethnicity are also at increased risk, but to a lesser extent. Copyright © 2018 ISUOG. Published by John Wiley & Sons Ltd.